Comfort performance of prescribed military uniforms experience response of some selected military men - Armero, Charlotte Posugac; Arribas, Lydia B. (1999.)
The study is all about the comfort performance of prescribed military uniforms based from wearing experiences of 50 military officers and 50 enlisted men. Descriptive method of research was used. Seven (7) military uniforms were chosen. Pair white alpha, pair white summer, black and white, and dungaree chambray for enlisted men, while white dress undress white, black and white, and working khaki for military officers. Self-administered questionnaire and personal interview were the methods used for data gathering. The researcher gathered the data both at Fort Bonifacio and Zambales. The respondents were chosen on a selective basis at the family's tailoring shop at Fort Bonifacio where she distributed the questionnaires. The researcher waited for military men to finished answering the questionnaires. On the other hand, at Zambales the questionnaires were given to one military officer who took charge in distributing questionnaires. The researcher returned for the questionnaires after 3 days. Also, the researcher had fabric testing in PTRI with regards the fiber composition of the fabrics for the uniforms. Fabrics are chambray, gabardine, denim, palm beach, and wool. Statistical tools used for analyzing the data obtained were frequency distribution and percentile methods. Majority of the respondents wants to change the fabrics used in their uniforms. Military men who participated in the study have enough pieces of uniforms. They have at least 7 pieces of uniforms, have one for each type. Also, military men preferred their uniforms to be individually tailored. Enlisted men have different ranking to military officers regarding to what is comfort to them. Summing up their respective frequencies, another ranking was obtained. As 1 being the highest and 5 being the lowest, they first considered ease for movement, second is that it is not warmth when worn, third is fabrics used, fourth is that it is not itchy, and fifth is that they look good in it. From the test report given by the Philippine Textile Research Institute (PTRI), 3 out of five are palm beach, gabardine, and wool. Denim is 100% cotton, while chambray has a blend of 68.4% polyester and 31.6% cotton.
Thesis (BSCT)--University of the Philippines Diliman.
Keywords: Military uniforms